HISTORICAL CHARACTERIZATION OF THE LABOR MARKET IN BRAZIL: FROM CONSOLIDATION TO LABOR REFORM - Souza, Danyelle Mestre de (2021)
This article aims to recover the essential aspects of the historical process of the labor market in Brazil, from the consolidation of this labor market to labor reform, more precisely the period from 1930 to 2017. The aim is to understand the particularities of a market of consolidated work in a peripheral/underdeveloped economy and the implications for the social and economic conditions of workers. Methodologically, it is a theoretical text, realized through the historical survey of the main contributions in the specialized literature. As a conclusion, it is highlighted that, despite important advances, several problems such as precariousness, informality, instability, lower wages, low degree of social protection, among others, remain as structural marks of the labor market of this society, in a context of promotion of public policies that do not show significant results in terms of improvements in the social and economic conditions of the working class, as is the case of the referred labor reform.